Febrile Seizure Simulation - Victor Cisneros; Alisa Wray (eScholarship Publishing, University of California, 2017)
Audience: This simulation session is appropriate for medical students, community physicians, or residents in emergency medicine, neurology, pediatrics, or family medicine. Introduction: Febrile seizures are the most common form of seizures in childhood; they are thought to occur in 2-5% of all children.1-3 Febrile seizures are defined as a seizure in association with a febrile illness in children without a central nervous system infection, previous afebrile seizure, known brain disorder, or electrolyte abnormalities. 1,2 They typically occur between 6 months and 18 months of age though they can occur up to 5 years of age.3 Febrile seizures are categorized as: simple (generalized seizure lasting less than 15 minutes in a child aged 6 months to 5 years, and less than 1 in a 24 hour period) or complex (a focal seizure or generalized seizure lasting greater than 15 minutes, or multiple seizures in a 24 hour period). 1,3 Treatment for febrile seizures is based on treating the underlying cause of the fever and giving reassurance and education to the parents.2 Mortality is extremely rare, and there is no difference in the patient's cognitive abilities after a febrile seizure, even when the seizure is prolonged.1 Objectives: At the end of this simulation session, the learner will be able to: 1) discuss the management of febrile seizures 2) discuss when placement of an advanced airway is indicated in the management of a febrile seizure 3) list the risk factors for febrile seizures 4) prepare a differential diagnosis for the causes of febrile seizures 5) educate family members on febrile seizures. Methods: This educational session is a high-fidelity simulation.